Analisis Perletakan Corewall pada Gedung Rumah Sakit UPT Vertikal yang Memiliki Ketidakberaturan Struktur - Januar Pradipta Lisdianto; Sumaidi; Nia Dwi Puspitasari (EduInovasi: Journal of Basic Educational Studies, 2025)
Construction of a Hospital in Surabaya. This hospital consists of 4 buildings, where the front building will be the medical check-up building and the 3 back buildings will be the cancer, brain and heart specialist buildings. In the brain specialist building there are several corewalls that were used during its construction. The re-planning of this building was carried out by changing the location of the corewall so that we could find out which corewall location was more efficient. In designing a corewall structure, there are several aspects that need to be considered, namely base reaction, earthquake period and drift between floors of the building. Analysis of the location of the corewall was carried out using the Excel and Etabs applications based on trial and error by moving the location of the main corewall away from and closer to the center of mass and strength. From the results of the analysis, it was found that there were 2 location modifications whose results were better than the others. In Modification 1 this is done by moving away from the center of mass and stiffness and in Modification 2 the location is changed by bringing the center of mass and stiffness closer. From the results of Modification 1, the base reaction in Direction X = 13011 kN and Direction Y = 10883 kN, the deviation between floors in Direction 58.34mm. From the results of the analysis carried out, it can be concluded that the results of modification 1 are with Spectra X = 13011 kN and Spectra Y = 10883 kN.